Gliosarcoma with Primary Skull Base Invasion. (8th December 2016) - Nguyen, Quoc-Bao D.; Perry, Avital; Graffeo, Christopher S.; Nesvick, Cody L.; Raghunathan, Aditya; Jentoft, Mark E.; O'Neill, Brian P.; Morris, Padraig P.; Morris, Jonathan M.; Van Gompel, Jamie J.
Abstract : Gliosarcoma is an uncommon variant of glioblastoma, which commonly demonstrates dural attachment. However, skull base invasion is rarely seen with this entity. Herein, we report a 44-year-old female patient diagnosed with primary intracranial gliosarcoma extensively invading the skull base and muscles of mastication. She presented to our institution with a three-month history of difficult right jaw opening and retro-orbital pressure and one week of severe right-sided postauricular headache. Head CT demonstrated a 6 cm mass with marked bony erosion. Brain MRI at a one-week interval more clearly characterized tumor extension through the right orbit and muscles of mastication, with overall growth to 7 cm and worsening midline shift. The patient underwent a right frontotemporal craniotomy for gross total resection. Pathology confirmed the diagnosis of gliosarcoma, IDH-wildtype (WHO grade IV). Her postoperative course was uneventful and she was discharged at preoperative neurologic baseline. To our knowledge, this is the third reported case of a primary intracranial gliosarcoma with direct invasion of skull base, brain parenchyma, and extracranial compartment. However, this is the first report case of primary GS invading the surrounding musculature and orbit. This case report highlights the rapid aggressiveness of gliosarcomas and further a prior undescribed radiographic and anatomic finding of skull base invasion with this entity.